Using MemTrax memory test to screen for post-stroke cognitive impairment after ischemic stroke: a cross-sectional study - Zhao, Xiaoxiao; Dai, Shujuan; Zhang, Rong; Chen, Xinjie; Zhao, Mingjie; Bergeron, Michael F.; Zhou, Xianbo; Zhang, Junyan; Zhong, Lianmei; Ashford, J. Wesson; Liu, Xiaolei (Frontiers in Human Neuroscience, 2023)
Background: Whereas the Montreal Cognitive Assessment (MoCA) and Addenbrooke's cognitive examination-revised (ACE-R) are commonly used tests for the detection of post-stroke cognitive impairment (PSCI), these instruments take 10-30 minutes to administer and do not assess processing speed, which is a critical impairment in PSCI. MemTrax (MTx) is a continuous recognition test, which evaluates complex information processing, accuracy, speed, and attention, in 2 minutes.Aim: To evaluate whether MTx is an effective and practical tool for PSCI assessment.Methods: This study enrolled acute ischemic stroke (AIS) patients who have assessed the cognitive status including MTx, Clinical Dementia Rating (CDR), MoCA, Neuropsychiatric Inventory (NPI), Hamilton Depression Scale (HAMD), Hamilton Anxiety Scale (HAMA), the National Institute of Health Stroke Scale (NIHSS), Modified Rankin Scale (mRS), and Barthel Index of Activity of daily living (BI) combined with the physical examinations of the neurologic system at the 90-day (D90) after the AIS. The primary endpoint of this study was establishing MTx cut-offs for distinguishing PSCI from AIS.Results: Of the 104 participants, 60 were classified to the PSCI group. The optimized cut-off value of MTx-%C (Percent Correct) was 78%, with a sensitivity and specificity for detecting PSCI from Non-PSCI of 90.0% and 84.1%, respectively, and an AUC of 0.919. Regarding the MTx-Cp (Composite Score =MTx-%C/MTx-RT), using 46.3 as a cut-off value, the sensitivity and specificity for detecting PSCI from Non-PSCI were 80.0% and 93.2%, with an AUC of 0.925. Multivariate linear regression showed that PSCI reduced the MTx-%C (Coef. -14.18, 95% CI -18.41~-9.95, p< 0.001) and prolonged the MTx-RT (Response Time) (Coef. 0.29, 95% CI 0.16~0.43, p< 0.001) and reduced the , p< 0.001).